جيوبوليتيك النفط في الجزائر وتحديات الانتقال إلى إستغلال الطاقات المتجددة Geopolitic of oil in Algeria and the challenges of transition to renewable energy - وناسي, لزهر; مزراق, منال (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
تهدف هذه الدراسة إلى تحليل الواقع الجيوبوليتيكي للنفط في الجزائر وإبراز الرهانات الجيوإستراتيجية والتحديات التي تواجهها نحو الإنتقال إلى استخدام الطاقات المتجددة، إذ أصبح من الضروري التفكير في سياسة طاقوية جديدة على ضوء الموارد الطاقوية غير الأحفورية التي تتمتع بها الجزائر، و تمكن من الدفع بالتنمية الاقتصادية الوطنية دون المساس بالمقدرات الطبيعية الناضبة. وعليه تتوخى الدراسة بداية بتحديد جيوبوليتيكا النفط في الجزائر، ثم تحليل التصور البديل للطاقات المتجددة والتعرض إلى رهانات الجزائر من جراء تبني سياسة الانتقال الطاقوي في ظل اتجاه كثير من دول العالم إلى اعتماد الطاقات المتجددة كإستراتيجية طاقوية تفرض تحديات أمام الطاقات الأحفورية إستكشافا وإنتاجا وتسويقا. This study aims to analyze the geopolitical reality of oil in Algeria, highlight the geostrategic stakes and the challenges it faces towards the transition to the use of renewable energies. It has become necessary to think about a new energy policy in light of the non-fossil energy resources that Algeria enjoys, and it was able to advance national economic development without prejudice to the depleted natural resources. Accordingly; The study aims at first by identifying the geopolitics of oil in Algeria, then analyzing the alternative vision of renewable energies, and exposing the bets of Algeria as a result of adopting an energy transition policy in light of the tendency of many countries of the world to adopt renewable energies as an energy strategy that poses challenges to fossil energies in exploration, production and marketing.